Further notes on the avifauna of the riau Archipelago - Seng, Lim Kim (KUKILA, 1997)
Further notes are supplied on the avifauna of Batam, Bintan and other islands in the Riau Archipelago that supplement those presented in Rajathurai (1996) in Kukila Volume 8.